Distribution and molecular characterization of ESBL, pAmpC β-lactamases, and non-β-lactam encoding genes in Enterobacteriaceae isolated from hospital wastewater in Eastern Cape Province, South Africa. - Folake Temitope Fadare (Public Library of Science (PLoS), 2021)
Globally, there is an increasing occurrence of multidrug-resistant (MDR) Enterobacteriaceae with extended-spectrum β-lactamases (ESBLs) and/or plasmid-encoded AmpC (pAmpC) β-lactamases in clinical and environmental settings of significant concern. Therefore, we aimed to evaluate the occurrence of ESBL/pAmpC genetic determinants, and some essential non-β-lactam genetic determinants in the MDR phenotypic antimicrobial resistance in Enterobacteriaceae isolates recovered from hospital wastewater. We collected samples from two hospitals in Amathole and Chris Hani District Municipalities in the Eastern Cape Province, South Africa, within October and November 2017. Using the matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF), we identified a total of 44 presumptive Enterobacteriaceae isolates. From this, 31 were identified as the targeted Enterobacteriaceae members. Thirty-six percent of these belonged to Klebsiella oxytoca, while 29% were Klebsiella pneumoniae. The other identified isolates included Citrobacter freundii and Escherichia coli (10%), Enterobacter asburiae (6%), Enterobacter amnigenus, Enterobacter hormaechei, and Enterobacter kobei (3%). We established the antibiotic susceptibility profiles of these identified bacterial isolates against a panel of 18 selected antibiotics belonging to 11 classes were established following established guidelines by the Clinical and Laboratory Standard Institute. All the bacterial species exhibited resistance phenotypically against at least four antibiotic classes and were classified as MDR. Notably, all the bacterial species displayed resistance against cefotaxime, ampicillin, nalidixic acid, and trimethoprim-sulfamethoxazole. The generated multiple antibiotic resistance indices ranged between 0.5 to 1.0, with the highest value seen in one K. oxytoca isolated. Molecular characterization via the Polymerase Chain Reaction uncovered various ESBLs, pAmpCs, and other non-β-lactam encoding genes. Of the phenotypically resistant isolates screened for each class of antibiotics, the ESBLs detected were blaCTX-M group (including groups 1, 2, and 9) [51.6% (16/31)], blaTEM [32.3% (10/31)], blaOXA-1-like [19.4% (6/31)], blaSHV [12.9% (4/31)], blaPER [6.5% (2/31)], blaVEB [3.2% (1/31)], blaOXA-48-like and blaVIM [15.4% (2/13)], and blaIMP [7.7% (1/13)]. The pAmpC resistance determinants detected were blaCIT [12.9% (4/31)], blaFOX [9.7% (3/31)], blaEBC [6.5% (2/31)], and blaDHA [3.2% (1/31)]. The frequencies of the non-β-lactam genes detected were catII [79.2% (19/24)], tetA [46.7% (14/30)], sulI and sulII [35.5% (11/31)], tetB [23.3% (7/30)], aadA [12.9% (4/31)], tetC [10% (3/30)], and tetD [3.3% (1/30)]. These results indicate that hospital wastewater is laden with potentially pathogenic MDR Enterobacteriaceae with various antibiotic resistance genes that can be spread to humans throughout the food chain, provided the wastewaters are not properly treated before eventual discharge into the environment.